Partial penile amputation due to Klingsor syndrome: A case report with a successful macroscopic reconstruction. (2020) - Syahrir, Syakri; Palinrungi, Muhammad Asykar; Kholis, Khoirul; Syarif,; Faruk, Muhammad; Christeven, Robert
Highlights: Traumatic penile amputation is a rare surgical emergency that requires immediate care. Most reported cases involve genital self-mutilation induced by psychiatric disorders. We report a successful proximal penile shaft amputation via macrosurgical techniques. Abstract: Introduction: Traumatic penile amputation is a highly uncommon surgical emergency that requires immediate intervention. Most reported cases involve genital self-mutilation induced by underlying psychiatric disorder, especially schizophrenia. The self-mutilation of external genitals in psychiatric patients, also known as Klingsor syndrome, is a rare form of urotrauma. Presentation of case: We present a case of partial penile amputation in a 46-year-old male with Klingsor syndrome admitted to the hospital 3 days after the incident. Urological examination revealed a subtotal cut of the penis, including the distal part of the mons pubis, dorsal and lateral parts of the penile skin, corpus cavernosum, and corpus spongiosum, as well as a partial bulbous urethra rupture. The penis remained suspended by only a thin ventral part of the penile skin. After macroscopic surgical replantation, the patient recovered well and could urinate without any symptoms of urethral stricture. The entire penis remained viable with minimal scarring at the surgical site, and penile erection could be achieved and maintained. Conclusion: The case demonstrates a rare instance of the successful proximal penile shaft amputation via macrosurgical techniques by an experienced urologic surgeon.